1991
DOI: 10.1007/bf00011885
|View full text |Cite
|
Sign up to set email alerts
|

Opalinidae in African Anura. II. Genera Protozelleriella n. g. and Zelleriella

Abstract: During 1988 and 1989, 409 specimens of southern African Anura, comprising 50 species in 9 families, were checked for opalinids in the cloaca. Protozelleriella devilliersi n. g., n. sp. was found in three of four Capensibufo rosei (Bufonidae); Zelleriella africana Sandon, 1938 in two of three Bufo angusticeps and one of 20 B. garmani (Bufonidae) plus three of 12 Phrynobatrachus natalensis, 12 of 19 Tomopterna cryptotis, seven of 14 T. delalandii, three of seven T. krugerensis and one of six T. natalensis (all R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…This variation is possibly attributable to physiological and/or ecological factors (Delvinquier et al, 1991b). Large specimens (trophozoites) were often found mixed with very small ones (presumably newly emerged from cysts) of the same shape.…”
Section: Commentsmentioning
confidence: 99%
See 4 more Smart Citations
“…This variation is possibly attributable to physiological and/or ecological factors (Delvinquier et al, 1991b). Large specimens (trophozoites) were often found mixed with very small ones (presumably newly emerged from cysts) of the same shape.…”
Section: Commentsmentioning
confidence: 99%
“…Metcalf (1923) 100/xm,Figs 54,55,58,60,63,[65][66][67]70,73,75,76,Figs 56,57,59,61,62,64,68,69,71,72,74,77, did not find any opalinids in one H. concolor from "southeast Africa", one "Rappia vermiculata" (now H. marmoratus, see Gorham, 1974) from Uganda and one "Megalixalus fornasinii" (now Afrixalus fornasinii, see Gorham, 1974;Frost, 1985) from Ukami, Tanzania, which he dissected. The other record of Cepedea, C. magna, is in Kassina and Semnodactylus (formerly included in the genus Kassina, see Delvinquier et al, 1991b). Kassina is also known to harbour Zelleriella (see Boisson, 1966Boisson, , 1967Delvinquier et al 1991b) and both genera were often found to occur together.…”
Section: Recorded It In Bufo Latrifronsmentioning
confidence: 99%
See 3 more Smart Citations